Research of Analysis and Dynamic Forecasting and Warning System of Flood Risk in Southeast Yin Plain of Ningbo - SUN Feifei; JIANG Yutian; REN Liliang; SUN Rufei; ZHAO Siyuan; ZHU Congfei (Renmin Zhujiang)
Predicting possible flood risks in advance and strengthening flood risk management can reduce losses caused by flood disaster. This paper simulates and calculates the inundation situation that may occur in Ningbo under the influence of heavy rain, storm surge and river flooding in southeast Yin plain of Ningbo through the mathematical model of Yongjiang Basin flood, selects 16 floods and 6 typhoons of different magnitudes for model calibration and calculation, draws urban flood risk maps on this basis to forecast and warn flood disasters, as well as designs a dynamic forecasting and warning system for flood risk in southeast Yin plain based on the model. It has been verified that the system is featured with good simulation accuracy and reasonable results, which can provide strong technical support for the dynamic warning and forecasting of flood risk in the plain.